Comparison of single-stage and two-stage ERCP Laparoscopic Cholecystectomy - Khan, Fatima Zehra; Ali, Mir Arsalan; Shafiq Ur Rehman; Ali Shah, Syed Mustafa; Nisar, Maheen; Abubaker, Zohaib Jawed (International Journal of Endorsing Health Science Research, 2020)
Background: Gallbladder surgeries are among the commonest major abdominal operations and to continuously improve the procedure many variants have developed that need evidence-based comparison in terms of frequency common bile duct (CBD) clearance, the mean operative time and hospital stay, and rate of adverse outcomes (post-operative pancreatitis). Through this study, we aimed to compare the surgical outcome of single-stage Endoscopic Retrograde Cholangio-Pancreatography (ERCP) with LC in comparison to two-stage ERCP. Methodology: This prospective study was conducted on a sample of 190 diagnosed patients (chosen via non-probability consecutive sampling) of cholelithiasis with choledocholithiasis, aged between 20 to 70 years who were scheduled to undergo surgery at the Ziauddin University Hospital, Karachi. The patients were divided into two equal groups (Group A: Single-stage ERCP & LC, and Group B: Two-stage ERCP followed by interval LC). After taking written informed consent, data pertaining to surgical outcome were recorded onto a pre-structured questionnaire and analyzed using SPSS Version 23.0. Results: The demographic and clinical characteristics of both the groups were similar and so were the success rates. Adverse events free and positive outcomes were reported in 95.79% and 90.53% of the patients in groups A and B respectively. Post-operative pancreatitis was reported more often among the patients of group B. The length of hospital stay and costs were lower among Group A patients despite the longer operative times in this group. Conclusion: Patients in group A yield better surgical outcomes, giving single-stage ERCP & LC the edge over two-stage ERCP followed by interval LC. Thus, single-stage ERCP & LC is recommended as the method of choice.